PENELITIAN EKOLOGI HUTAN DI PULAU NATUNA: STATUS HARA DAUN DAN SERASAH - Mirmanto, Edi (Research Center for Biology-Indonesian Institute of Sciences, 2015)
Forest ecological study with special attention to leaf and litterfall nutrient status has been conducted in several forest types at Natuna Island, Riau Archipelago. Ten plots have been setup which distributed in several forest type areas. Fresh leaf was collected from some dominant tree within the plots, whereas fallen leaves collected from litter traps.Nutrient content especially for N, P, K and Ca analyzed from all combined species of both fresh and fallen leaves.Results of chemical analyses showed that all fallen leaves mineral element concentration, except for Ca,were lower than that in fresh leaf. Presentage of retranslocation of both nitrogen and phosphorus tended to be similar to some earlier studies in several tropical forests. Nitrogen and phosphorus were suspected to be limiting factors of forest growth in this area.